A moral householding perspective on the sharing economy. (20th November 2018) - Laamanen, Mikko; Wahlen, Stefan; Lorek, Sylvia
Abstract: In this paper, we scrutinise the sharing economy from a moral householding perspective and evaluate the moral justifications for a sustainable form of the sharing economy. We consider the emergence of normative moral justifications through householding practices that rest on local mobilisation of people in defence of communities and commitments against the adverse impacts of neoliberal market capitalism. Our perspective draws on Karl Polanyi's conceptualisation of householding, that is, autarchic, communistic provision in a closed community. Using timebanking as an example, we illustrate how a moral sharing economy can be mobilised in collective battles against the current neoliberal system of economic crisis. We contribute to the amassing sharing economy literature emphasising a central, yet missing element of the current discourse: householding as practices creating self-sufficiency and autonomy as well as combining both kin and stranger.